Review of Backstop Land, by Glenn Patterson - Hedwig Schwall (Review of Irish Studies in Europe)
Review of Backstop Land, by Glenn Patterson (London: Head of Zeus/Apollo, 2019) ISBN 9781838932039,240 pp., £7.99 (paperback)